Data Visualization of Research Publications of IIB Darmajaya Lecturers - Destiawan Destiawan; Eko Zulkaryanto; Muhammad Fahmi Hafidz; Yoni Hisbullah; M S Hasibuan (Prosiding International conference on Information Technology and Business (ICITB), 2021)
Data visualization is now very important to understand data and can be used for decision making. Effective visualization assists users in analyzing and reasoningabout data and makes complex data accessible, understandable and useful. Users can perform analysis, such as making comparisons or understanding causality. The Indonesian government has upgraded the status of the IIB Darmajaya Research Institute so that it must increase its publications. IIB Darmajaya currently requires a system to determine the achievements of lecturers' research publications in datavisualization. Visualization tools are increasingly being used, such as Microsoft Power BI, Google Chart, Tableau, Zoho Analytics, Datawrapper, Infogram, Google Data Studio, and others. Currently, Google Data Studio is increasingly beingused since its release in 2016. Google Data Studio allows developers to easily visualize data without having to be a data scientist. IIB Darmajaya currently does not have a system to visualize published research publication data. This study usesGoogle Data Studio in developing a data visualization system for lecturer research publications that have been published on Scopus, Google Scholar, and Web of Science (WOS). The steps taken in this research are requirements analysis, collecting data, preparing data, and implementation. This study succeeded in developing a data visualization system for lecturer research publications for IIB Darmajaya and is expected to be a source of information on current achievementsand a reference for future decision making. Keywords— data visualization, google data studio, research publications